UROLOGICAL COMPLICATIONS IN PATIENTS WITH PROLONGED ANURIA BY RENAL TRANSPLANTATION - A. V. Kolsanov; B. I. Kharitonov; I. A. Bardovskiy (Креативная хирургия и онкология, 2017)
145 recipients of kidneys analyzed, operated from 2006  to 2010. Of these 68 (46,%) patients with anuria period of more than 3 years. A method for treating patients with prolonged anuria in renal transplantation consists of three phases: preoperative, perioperative, and postoperative. The study is divided into three groups. The first group of patients was with prolonged anuria without urological examination and treatment. The second group with prolonged anuria, but carried out perioperative and postoperative phases. In the third group  were held all three stages of treatment for patients with prolonged anuria in renal transplantation. This study proves the effectiveness of the proposed method of treatment. Improved results in both immediate and late postoperative period. When you run the full course of the proposed method of diagnosis and treatment of patients with prolonged anuria in renal transplantation to reduce the number of urologic complications by 13% over a three year period of observation.